Logistic Curve Models of CO2 Accumulation - David Levinson (Findings)
This article explores the use of logistic-shaped diffusion curves (S-Curves) to predict the accumulation of atmospheric CO2. The research question here is whether forecasts using logistic curves are stable, that is, do they predict consistently over time with different amounts of data? Using data from the Keeling Curve, we find that the best-fit maximum atmospheric CO2 predicted varies significantly by model year when estimating models limited to data available until that point in time. More recently estimated models are more consistent, all indicate that CO2 accumulation will continue in the absence of an external shock to the system.